(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper explores the role of technology and online platforms in enhancing English language learning. With the rapid digitalization of education, tools such as Duolingo, Quizlet, and Kahoot have become widely used to supplement traditional teaching methods. The study discusses the benefits of technology in promoting learner autonomy, motivation, and engagement, as well as challenges such as digital divide and over-reliance on online resources. Findings suggest that when integrated effectively, technology significantly contributes to improving linguistic competence and 21st-century skills.